STRATEGI PEMASARAN TANAMAN HIAS DENGAN PENDEKATAN ANALISIS SWOT - Utomo, Mansur Wahyu; Qomariyah, Siti Nur (Exact Papers in Compilation (EPiC), 2021)
This writing aims to determine the right marketing strategy to increase sales in terms of SWOT Analysis, EFAS, IFAS, and the Grand Strategy Matrix at Brother Farming, Badang Village, Ngoro District, Jombang Regency. The location of this research was chosen intentionally (purposive sampling) with the consideration that Brother Farming, which had only been established for two years, was already widely known by the public. This research was conducted in Badang Village, Ngoro District, Jombang Regency in March - April 2021. The data processing technique used in this study used primary data and secondary data. Primary data were obtained by interview and documentation with the owner of Brother Farming, Badang Village, Ngoro District, Jombang Regency. While secondary data includes data presented by relevant agencies, archives in accordance with the needs of researchers. The analysis used in determining Brother Farming's ornamental plant marketing strategy includes evaluation of internal factors, evaluation of external factors, IFAS matrix, EFAS matrix, SWOT matrix and Grand Strategy matrix. The results of the research in 2021 include IFAS internal factors (8 points strength and 5 points weakness), EFAS external factors (7 points opportunity and 5 points threat) while the grand strategy matrix of Brother Farming's position, Ngoro District, Jombang Regency is in quadrant I, This shows a very profitable situation because Brother Farming, Ngoro District, Jombang Regency has strengths and opportunities so that they can take advantage of existing opportunities to increase sales.